The Service Desk Handbook - A Guide to Service Desk Implementation, Management and Support - Nair, Sanjay (IT Governance Publishing, 2020)
The Service Desk Handbook - A guide to service desk implementation, management and support provides operational guidance for implementing, managing and supporting service desks in the enterprise. It will help service desk teams in adopting ITIL® to accomplish their tasks while making the necessary adaptations as per their organisation's needs.